PERAN AUDITOR TERHADAP PRAKTIK EARNINGS MANIPULATION DI KALANGAN PERUSAHAAN LQ45 - Reskino Reskino; Siti Kurniasih (JMB : Jurnal Manajemen dan Bisnis, 2023)
Using the analysis of fraud theory developed by Reskino (2022), this study examines the relationship between employee diff, the big 4 auditors, auditor switching, the ethnic composition of directors on the board, and the ethnic composition of the audit committee on earnings manipulation. 55 samples of company data that were consistently included in the IDX LQ45 list from the Indonesia Stock Exchange (IDX) were used with the purposive sampling method. Using the Modified Jones Model with ROA which is believed to produce a higher adjusted R2 than the Modified Jones Model. The results of the research show that earnings manipulation that earnings manipulation still occurs within the company in the presence or absence of employee diff, auditor switching, Indonesian national board of directors and audit committee. However, the role of the big 4 auditors can reduce earnings manipulation. This research implies that it is hoped that regulators can issue regulations regarding disclosing more non-financial measures in financial statements so that users of financial reports can directly compare financial and non-financial measures. By knowing non-financial indicators in LQ45 companies, it is hoped that they conciseness make appropriate policies to mitigate risk in LQ45 companies.